Learners and Teacher Toward The Problem-Solving Based Learning Media - Marsela, Vitria; Subadiyono, Subadiyono; Suhendi, Didi (Universitas Pendidikan Ganesha, 2021)
Many students still have difficulty developing their ideas about explanatory texts while undergoing the learning process in class. This study aims to analyze the needs of students and teachers for the development of learning media in the form of animation writing explanatory texts based on problem-solving. This research is qualitative research that analyzes the first and design stages of research and development. The things that were analyzed were the needs of students and teachers for animated learning media to write problem-solving-based explanatory texts. From the data collected through questionnaires and interviews with 33 students and 1 Indonesian teacher. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The research results show that animated learning media about problem-solving-based explanatory text writing can be an innovative medium for learning activities and can support students' and teachers' needs. This learning media is beneficial for both parties and can be accessed offline. Thus, learning media can be an alternative for the needs of teachers and students in learning and teaching writing explanatory texts.